PENGELOLAAN PANTI ASUHAN SANMA PASANG SURUT: METODE PENDAMPINGAN ANAK - Agustinus Riyanto; Fransiska Soejono; Prisca Yeniyati; Theresia Sunarni; Suzzana Winda Artha Mustika; Stefanus Halim (Jurnal Abdimas Musi Charitas, 2018)
The purpose of this community service activity is first, to provide additional knowledge and experience about the mentoring method that can be used for the Children of the Santa Maria Orphanage. The second objective is to provide additional knowledge, skills and insight into the values of goodness to the Children of the Orphanage St. Maria (SanMa). The activities were conducted in the workshop of the UKMC lecturers team for child counselors who were packed in the form of debriefing for the child's companion. Assistance for foster children is packaged in the form of games, the development of mindset through inspiring film / video, as well as facilitation skills for foster children under the age of 5 years through the activities of drawing and coloring together. The division of questionnaires is done at the end of the activity as feedback on activities that have been done. Positive responses of participants to the activities performed were seen from the interviews and filling questionnaires.